Fundamentals of Entrepreneurship ENT 300 : Rajah Putih Restaurant / Wellance Nicholas Ningkan...[et al.] - Nicholas Ningkan, Wellance; Idris, Baiman; Muhammad, Tarmiezy; Abd Mutalib, Aiman; Ahmad Saifuddin, Muhammad Lutfi (2019)
he name of our company is Rajah Putih Restaurant. The business is in the form of partnership, which consists of four members. Each partner contributes certain amount of capital as agreed in our agreement. Our business activity focuses on providing the food and beverages based on Sarawakian Traditional Food . Our company are located at Kuching Waterfront. All partners are entitled to participate in the business management and agreed that Wellance anak Nicholas Ningkan as our General Manager and Baiman Bin Idris Administration Manager, Muhammad Tarmiezy as our Financial Manager, Muhammad as Aiman Bin Abd Mutalib and Muhammad Lutfi Bin Ahmad Saifuddin as our Operational Manager and Hilal Aswad Bin Junaidi as our Marketing Manager. The team is lead by General Manager and assisted by other managers. The General Manager is responsible in planning, organizing, leading and controlling. Administration Manager will responsible for the job related to administration such as planning and arranging the remuneration schedule of wages, salary and day of work or shift. Financial Manager will handle financial matters such as preparing budgets and financial statements for the expenses of each department. The Marketing Manager is responsible of preparing the marketing plan such as identifying the targeted market, determining the market size, competitors, market share, developing sales forecast and marketing strategies. Lastly, the Operation Manager will control and monitor our business. All workers that work in our company will be supervised by operational manager. This will produce quality control and productivity to our company. GENERAL MANAGER. ACKNOWLEDGEMENT Firstly, we would like to thank the Almighty God for blessing us in order to complete our business plan successfully. Without God's blessing, we believe that we will never complete this business plan on time. We are feeling grateful that we are managing to run the business after a lot of perspiration and hard work to all of this. III Besides putting our full commitment, there is one person that we want to give a very big thank to him, who is En. Johari Bin Abdullah because of his effort and full commitment in order to teach us the way to be an entrepreneur. If we do the business without his guidance for sure we will not able to finish this project. He was a great lecturer with clear understanding and also a good channel of giving examples and information based on his experience. We also want to thank everybody who involved direct and indirectly towards our projects especially our classmates. Even we are not the same group but we always change opinion among our groups. In addition, we also like to appreciate the organization that involve in our project, they are all very helpful in giving information and opinion which close related to our business. Once again, we would like to thank everyone that had helped, support and motivating us either direct and indirectly. Their contribution is the most valuable asset of this small but useful study.